Scenedesmus obliquus as feedstock for biohydrogen production by Enterobacter aerogenes and Clostridium butyricum - Batista, Ana Paula (2014)
Hydrogen (H2) gas is seen as an ideal future energy carrier because it is easily converted into electricity in fuel cells, liberates a large amount of energy per unit mass, and generates no air pollutants. In this work, biological hydrogen (bioH2) was produced from the microalgal biomass of Scenedesmus obliquus which was used as a substrate for the fermentation by Enterobacter aerogenes ATCC 13048 and Clostridium butyricum DSM 10702. The bioH2 produced by each strain was assessed for different S. obliquus biomass concentrations, using both dried (5% moisture) and ‘‘wet’’ (69% moisture) biomass. The highest bioH2 production yields obtained were 57.6 mL H2/g VSalga from 2.5 galga/L by E. aerogenes and 113.1 mL H2/g VSalga from 50.0 galga/L by C. butyricum. The bioH2 production rates, and biogas purity attained by using the wet biomass as a fermentation substrate were similar or higher than those obtained with the dried microalga. This means that the drying step is not needed and therefore saves considerable energy as this is one of the highest energy demanding stages when using this feedstock in fermentations for biofuels production.